The Pageant of Literature: A Second Book of Poetry - Peterson, R. Stanley (New York The Macmillan Company, 1964)
As you read the poems in this book, you will find yourself drawn into the web of poetic composition. The emphasis in this book is on the study of poems rather than on the study of poetry.
Keywords: Poetry